Bridging the digital divide: a case study of a collaboration between a metropolitan municipality and a non-profit organisation - Seifert, Natalie (Stellenbosch : Stellenbosch University, 2017)
Thesis (MCom)(MPA)--Stellenbosch University, 2017.